Digital Innovations for the Coffee Value Chain in Honduras and Guatemala: A scoping study - Melo, Jenny; Wiegel, Jennifer Rebecca (CGIAR System Organization, 2023)
This work offers a synthesis of the current digital technologies available for coffee that are relevant to the context of Honduras and Guatemala. It results from desk research considering current literature (grey and academic) and interviews with actors selling digital technologies to the Centro American coffee sector. This summary is organized into four parts. First, there are introductory concepts on digital technologies applied in agriculture, useful to have a common ground; Three aspects are covered here: what are digital technologies, their potential, and what socio ethical aspects should be considered when promoting these technologies. Second, there is an overview of digital technologies in Honduras and Guatemala. Third, there is an overview of the digital technologies currently available in the coffee sector. In this section, twenty three technologies are presented and organized by service types, level of development, and seller information. Four, there are comments on the potential impactful technologies, a review of aspects to consider when supporting these technologies, and conceptual and methodological recommendations useful for the future work of the team testing digital technologies in the field. This work was developed in the context of the Initiative Rethinking Food Markets and Value Chains for Inclusion and Sustainability, developed by the Bioversity CIAT Alliance and the CGIAR support.